2019
DOI: 10.1177/0098628319872411
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Inspired Choices for Teachers: Team-Based Learning and Interactive Lecture

Abstract: Research on team-based learning (TBL) generally supports its effectiveness over “traditional” lecture. In practice, however, lecturing rarely consists of teachers exclusively talking at their students, as many incorporate a variety of strategies to encourage active processing. This study compared an interactive lecture style with TBL on student performance. Generally, the results indicate that there are differences in particular aspects of course performance across conditions depending upon grade point average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Active teaching methods are used in the educational process together with Interactive teaching methods. ITMs correspond to a person-centered approach, as they are aimed at all participants' interaction with each other during educational process in order to exchange information, to solve problems in groups, and to simulate situation (Estrada et al, 2020;Gopinath, 2015;Jakobsen & Daniel, 2019…”
Section: Resultsmentioning
confidence: 99%
“…Active teaching methods are used in the educational process together with Interactive teaching methods. ITMs correspond to a person-centered approach, as they are aimed at all participants' interaction with each other during educational process in order to exchange information, to solve problems in groups, and to simulate situation (Estrada et al, 2020;Gopinath, 2015;Jakobsen & Daniel, 2019…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found no significant difference in grades when comparing lectures with TBL if the variable of attendance is constant [ 22 ]. A recent study revealed that high achievers performed well in TBL and low achievers in IL even though there is no difference in students' overall performance using IL and TBL [ 23 ]. In another study, TBL was found to be superior in retaining knowledge compared with lecture as an instructional strategy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rather than comparing a new technique to business as usual, Jakobsen and Daniel (2019) recently compared a fairly well-documented college-level teaching strategy, team-based learning, with a "new" technique. The new technique worked just as well as the highly supported strategy.…”
Section: Significance: When Non-significant Ismentioning
confidence: 99%